Superacid-Promoted Dual C–C Bond Formation by Friedel–Crafts Alkylation/Acylation of Cinnamate Esters: Synthesis of Indanones - Ramulu, Bokka Venkat; Niharika, Pedireddi; Satyanarayana, Gedu (Synthesis, 2015)
Dual C–C bond formation was accomplished in one pot for the synthesis of a wide variety of indanones mediated by triflic acid. The reaction proceeds via an initial Michael-addition-type Friedel–Crafts alkylation followed by intramolecular acylation (cyclization). Significantly, the method was also successfully employed on more reactive β-diarylcinnamates using slightly different conditions.
Keywords: cinnamates; Friedel–Crafts; indanones; alkylation; benzophenones